Distinct pharmacological profiles of ORAI1, ORAI2, and ORAI3 channels. (November 2020) - Zhang, Xuexin; Xin, Ping; Yoast, Ryan E.; Emrich, Scott M.; Johnson, Martin T.; Pathak, Trayambak; Benson, J. Cory; Azimi, Iman; Gill, Donald L.; Monteith, Gregory R.; Trebak, Mohamed
Graphical abstract: Highlights: ORAI channel isoforms are distinctly affected by pH and various pharmacological inhibitors and activators. Synta66 inhibits ORAI1 and potentiates ORAI2 whereas IA65 potentiates ORAI1 and inhibits ORAI2. ORAI heteromerization through concatenated constructs shapes the pharmacological profiles of CRAC channels. Distinct ORAI isoform pharmacology would help determine the contribution of each isoform to CRAC channels in primary cells. Abstract: The ubiquitous Ca 2+ release-activated Ca 2+ (CRAC) channel is crucial to many physiological functions. Both gain and loss of CRAC function is linked to disease. While ORAI1 is a crucial subunit of CRAC channels, recent evidence suggests that ORAI2 and ORAI3 heteromerize with ORAI1 to form native CRAC channels. Furthermore, ORAI2 and ORAI3 can form CRAC channels independently of ORAI1, suggesting diverse native CRAC stoichiometries. Yet, most available CRAC modifiers are presumed to target ORAI1 with little knowledge of their effects on ORAI2/3 or heteromers of ORAIs. Here, we used ORAI1/2/3 triple-null cells to express individual ORAI1, ORAI2, ORAI3 or ORAI1/2/3 concatemers. We reveal that GSK-7975A and BTP2 essentially abrogate ORAI1 and ORAI2 activity while causing only a partial inhibition of ORAI3. Interestingly, Synta66 abrogated ORAI1 channel function, while potentiating ORAI2 with no effect on ORAI3. CRAC channel activities mediated by concatenated ORAI1-1, ORAI1-2 and ORAI1-3 dimers were inhibited by Synta66, while ORAI2-3 dimers were unaffected. The CRAC enhancer IA65 significantly potentiated ORAI1 and ORAI1-1 activity with marginal effects on other ORAIs. Further, we characterized the profiles of individual ORAI isoforms in the presence of Gd 3+ (5μM), 2-APB (5 μM and 50 μM), as well as changes in intracellular and extracellular pH. Our data reveal unique pharmacological features of ORAI isoforms expressed in an ORAI-null background and provide new insights into ORAI isoform selectivity of widely used CRAC pharmacological compounds.